Minat Memesan Kembali Jasa Transportasi Online - Jovi - Iristian (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
The number of smartphone users that continues to increase over time seems to be in line with the increasing number of users of online transportation services from the web and applications. Technology that is built by understanding the experience of its users has changed people's behavior in traveling and carrying out daily activities. The vehicle booking application in particular has been a breakthrough because it allows a convenient pick-up and delivery system at an affordable price. The purpose of this study was to determine brand experience, emotional connection to the brand and brand image to interest in ordering back online transportation services. The population is customers who use the online transportation service